Perianal Abscess Cavity Packing Versus No Packing A Randomized Control Trial - Lajpat Rai, Muhammad Ali Ghufran, Khursheed Ahmed Samo, Munawar Hussain Mangi, Jahanzaib Babar, Summaya Saeed (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the outcome of perianal abscess cavity packing versus no packing following I&D. The primary objective is to compare postoperative pain. The secondary outcomes were the number of follow-up visits, fistula formation, wound healing time and abscess recurrence. Methods: A randomized clinical trial was conducted at Dr Ruth K. M. Pfau Civil Hospital Karachi from March 2020 to July 2021. Results: 70 participants’ data were analyzed, 35 in the packing group (control) and 35 in the no packing group (intervention). The preoperative and postoperative pain scores at 48 hours are stastatistically not significant. The mean postoperative pain score showed a significant difference at two weeks, showing that the group receiving no packing experienced less intense pain. The mean wound healing time was 44.09 days in the packing group and 26.91 days in no packing group (p=0.001). The occurrence of fistula in ano was 2.8% in the packing group and 5.7% in no packing group (p=0.55). Abscess recurrence was 14.2% in the packing group, while 0% in no packing group (p=0.02). Conclusion: This study revealed that the no-packing technique is superior in decreasing postoperative pain and patient satisfaction. Keywords: Perianal Abscess, Randomized trials, No packing, Packing, Anorectal disease